An advanced GIS based hazard index tool for an automated health risk assessment framework - Adiguzel, Fatih; Karadeniz, Enes; Karli, Rukiye Gizem Oztas; Zhang, Maomao; Tabar, Mehmet Emin; Kaya, Asir Yuksel; Alshammari, Fahad Sameer (Nature Portfolio, 2026)
In this study, the spatial distribution of heavy metals (Pb, Cd, Cr, Ni, Co, Zn) found in street dust in the city of Adana and their potential effects on human health were examined using a risk assessment approach. Street dust samples were taken from 80 locations chosen to reflect areas with heavy traffic and industrial activity, and these samples were analyzed in the laboratory. The measured heavy metal concentrations were then mapped using the IDW method. Average Daily Dose (ADD), Hazard Quotient (HQ) and Hazard Index (HI) were calculated based on ingestion, inhalation and dermal exposure according to models provided by the US EPA. The results showed that heavy metal concentrations were higher in industrial areas, high traffic areas and densely populated areas than in other areas. Children's HI values ranged from 0.20 to 1.99, and exceeded 1 in the hotspot areas highlighted on the map, suggesting a potential for long-term non-carcinogenic health effects. For adults, HI values ranged from 0.027 to 0.34 and remained below 1, indicating a lower risk. Additionally, in the ArcGIS Pro environment, a unique Health Risk Assessment tool was also created to compute HQ and HI values and map their spatial distribution. This tool addresses a significant gap in the literature by integrating all exposure pathways to conduct risk analyses in a timely, reproducible, and user-friendly manner.
Keywords: Arcgis Pro; Hazard Index; Health Risk Assessment; Environmental Health; Automated Assessment Tool; Environmental Health Informatics; Climate Action